LITERASI KESEHATAN IMUNISASI DASAR LENGKAP PADA IBU BALITA DI DESA SUKAMENANG KABUPATEN MUARA ENIM SUMATRA SELATAN - Farida Kumalasari; Yusri; Rico Januar Sitorus; Najmah; Rini Mutahar; Feranita Utama; Danny Kusuma Aerosta; Rini Anggraini (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Based on WHO data in 2021, as many as 25 million children did not receive complete immunizations globally. Meanwhile, in Indonesia, the number of children who have not been fully immunized from 2017 to 2021 is 1,525,936 children. Basic immunization is one of the infectious disease prevention programs for children. Infectious diseases such as measles, polio, hepatitis B, diphtheria, pertussis (whooping cough), tetanus, and tuberculosis are included in the Diseases That Can Be Prevented by Immunization (PD3I). Through basic immunization health literacy, the public can understand the scientific facts that underlie the effectiveness and safety of vaccination. The target to be achieved in community service activities by the Epidemiology team of the Faculty of Public Health, Sriwijaya University is to increase understanding of complete basic immunization in mothers of toddlers in Sukamenang village so that the coverage of complete basic immunization in the village can reach 100% as its output. The activity method is carried out in the form of counseling and discussion (question and answer) to mothers of toddlers at the integrated health post about complete basic immunization, distribution of leaflets to activity participants. And cognitive test (Pre Test and Post Test). As an indicator of the success of complete basic immunization health literacy activities. The results of this health literacy program have succeeded in increasing the understanding of mothers of toddlers in Sukamenang Village regarding complete basic immunization.